2020
DOI: 10.1101/2020.09.30.20200493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Vivo Mitochondrial ATP Production Is Improved in Older Adult Skeletal Muscle After a Single Dose of Elamipretide in a Randomized Trial

Abstract: Background: Loss of mitochondrial function contributes to fatigue, exercise intolerance and muscle weakness, and is a key factor in the disability that develops with age and a wide variety of chronic disorders. Here, we describe the impact of a first-in-class cardiolipin-binding compound that is targeted to mitochondria and improves oxidative phosphorylation capacity (Elamipretide, ELAM) in a randomized, double-blind, placebo-controlled clinical trial. Methods: Non-invasive magnetic resonance and optical spec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…It also promotes skeletal muscle wasting and appears in various models of muscle atrophy, including disuse, diabetes, and aging [ 53 , 54 , 55 , 56 ]. It is well known that mitochondrial content and ATP production capacity play an important role in maintaining normal mitochondrial function and muscle function [ 57 , 58 ]. A previous study reported that DEX induces muscle atrophy by promoting mitochondrial dysfunction through decreased ATP production as well as reduced mitochondrial content in C2C12 myotubes compared to the native state [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also promotes skeletal muscle wasting and appears in various models of muscle atrophy, including disuse, diabetes, and aging [ 53 , 54 , 55 , 56 ]. It is well known that mitochondrial content and ATP production capacity play an important role in maintaining normal mitochondrial function and muscle function [ 57 , 58 ]. A previous study reported that DEX induces muscle atrophy by promoting mitochondrial dysfunction through decreased ATP production as well as reduced mitochondrial content in C2C12 myotubes compared to the native state [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Developing tools to precisely control ATP/ADP levels in both the cytosol and in the mitochondrial matrix, as well as control over Δψ m , will be necessary first steps in elucidating more detail in experimental models. However, emerging evidence suggests that directly intervening on ANT function is possible to facilitate better understanding of mitochondrial energetics in vivo in the context of aging [18, 55]. Similarly, targeting IF1 in mammalian cells has been informative for probing the mechanisms of nutrient-sensing signaling and Δψ m [56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…This limitation makes it difficult to compare to other aging interventions such as those in the National Institute of Aging Intervention Testing Program (ITP). Recent evidence in older humans demonstrated that a single treatment with ELAM improved in vivo mitochondrial function immediately after treatment and returned to placebo level a week later ( 11 ). However, this study suggested that effects on skeletal muscle fatigue resistance were elevated a week after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that the mitochondrial-targeted peptide elamipretide (ELAM), previously referred to as Bendavia, MTP-131, and SS-31, is an effective intervention to reverse skeletal muscle ( 5, 6 ), cardiac ( 7 ), kidney ( 8 ), retina ( 9 ), and cognitive dysfunction in aged mice ( 10 ). Clinical trials in aged humans demonstrated improvements of in vivo mitochondrial energetics after a single treatment ( 11 ). This improvement was short-lived, consistent with the short half-life of the compound( 5 ).…”
Section: Introductionmentioning
confidence: 99%